Effects of a Mental Health Intervention in Athletes: Applying Self-Determination Theory - Shannon, Stephen; Hanna, Donncha; Haughey, Tandy; Leavey, Gerard; McGeown, Conor; Breslin, Gavin (Frontiers in Psychology, 2019)
Introduction: Many sport associations have responded to mental health issues in sport through the inclusion of self-management programs, such as mindfulness training, which may improve well-being through increasing one’s competence in self-regulating stressors. Yet, the mechanisms accounting such changes lack a theoretical basis, particularly in athletes. Aim: To determine the effect of a mental health intervention comprising a mindfulness program for promoting well-being, reducing stress, and increasing competence in mental health self-management. This is the first study among athletes to test the mechanisms of change in a mindfulness program using Self-Determination Theory (SDT). Methods: A 2 (groups) × 2 (time-point) non-randomized controlled trial was conducted, and between-groups baseline differences were firstly assessed. Two competing regression models assessing singular and serial indirect mediating mechanisms were conducted, in which mindfulness (Model 1) and competence satisfaction (Model 2) were both tested as primary and secondary mediators predicting change scores in stress and well-being. Demographic variables (i.e., gender, age) were controlled for in the analyses. Results: Two hundred and thirty-eight student athletes (mean age = 20.47 years, SD = 3.30, 57.6% = males) participated, with 108 in the intervention group who received an instructional workshop, and a home-directed mindfulness program comprising daily meditation sessions. No baseline differences were found between intervention and control groups. In Model 1, mindfulness was not directly enhanced by the intervention, subsequently resulting in no indirect effects on competence, stress and well-being. In Model 2, the intervention was directly related to positive changes in competence (β = 0.39, p < 0.05), subsequently resulting in indirect effects on mindfulness awareness (β = 0.07, p < 0.05), stress (β = −0.06, p < 0.05), and well-being (β = 0.05, p < 0.05). In addition, serial indirect effects for the intervention on stress were present through competence and mindfulness awareness in sequence (β = −0.02, p < 0.05), and; on well-being through competence, mindfulness awareness, and stress in sequence (β = 0.01, p < 0.05; R2 = 0.54). Conclusion: Mindfulness-based mental health interventions may be effective at reducing stress and promoting well-being in athletes, with the caveat that attention is given to the inclusion of mental health competence promotion in program design. However, it remains unclear whether increasing mindfulness itself can exert additional salutary effects. Our findings have an important bearing on how mindfulness programs are developed within athlete mental health interventions.